Resistance training for metabolic syndrome: Part II - Sorace, P.; Ronai, P.; Churilla, J. R. (Strength and Conditioning Journal, 2013)
The special populations column provides a brief overview of metabolic syndrome (mets) and the potential benefits resistance training (RT) can have on preventing and managing mets. This column will provide scientifically supported RT recommendations for the prevention and managements of mets,